Strategies for talent engagement and retention of Brazilian Nursing professionals - Francine Schlosser; Marcia Carvalho de Azevedo; Deborah McPhee; Jody Ralph; Hanna Salminen (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To reflect on how human resource health managers and talent managers may engage and retain experienced nursing professionals in Brazil. Methods: Reflection based on studies on global and Brazilian-specific nursing professionals and retention, before and during the COVID-19 pandemic. Results: The pandemic worsened working conditions for all health professionals. Nursing professionals were particularly affected. Nurses have been viewed as "heroes" and "essential" frontline workers during the COVID-19 pandemic. However, despite the universal praise for their efforts, it seems uncertain if they were actually considered and managed like talent. Final considerations: In order to develop a sustainable healthcare system supported by sufficient experienced nursing talent, healthcare human resource managers and talent managers must develop and implement impactful nursing talent retention and engagement strategies. We highlight possible strategies targeting experienced nursing talent that will help to sustain the Brazilian healthcare system, post-pandemic.